Ex-post evaluation of Territorial Integrated Projects in Italy: an empirical analysis at firm level - Alessandro Cusimano; Fabio Mazzola (European Regional Science Association (ERSA), 2013)
This paper focuses on the evaluation of an incentive program for firms implemented in southern Italy during the last decade. In the framework of the policy instruments aimed to reduce territorial disparities, and to support local development, territorial integrated projects (TIP) constituted a new operational mode to implement the Regional Operational Programmes. A TIP is defined as a ?set of inter-sectorial actions, closely consistent and linked among them, which converge towards the common objective of territorial development and justify a unitary implementation approach'. The resources allocated for each TIP may be aimed at three types of interventions such as infrastructures, public actions and aid schemes. Through an empirical analysis on the resources allocated to aid schemes, this paper investigates, at firm level, the possible different performances of the beneficiaries of subsidies provided by TIP, as compared to non-beneficiaries. In particular a subset of firms which received subsidies in the period 2002-2007 is considered, through the implementation of an empirical analysis which uses Propensity Score Matching methods and a Difference-in-Differences approach jointly. In detail, the treated group of firms receiving subsidies is compared with a control group, constructed among firms having similar characteristics to treated firms, but which did not receive any subsidization. Every treated firm is matched with one or more firms belonging to the control group, on the basis of the value assumed by the Propensity Score, given the pre-treatment characteristics of firms. After the calculation of the Propensity Score, the effect of the policy is determined through the computation of the Average Treatment Effect on the Treated (ATT) by using Nearest-Neighbor Matching, Radius Matching, Kernel Matching and Stratification Matching methods. The ATT is computed with respect to the difference between a post-treatment period and a pre-treatment period, and refers to selected outcome variables such as EBITDA, EBITDA per employee, ROI, Number of employees and Value added per employee. Results show mixed evidence on the effect of the program.
Keywords: R58; L5; H71; 330; ex-post evaluation; local development; public subsidies; propensity score matching; difference-in-differences